2015
DOI: 10.4018/978-1-4666-8510-9.ch005
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Business Process Reengineering in the Modern Business World

Abstract: This chapter reveals the role of business process reengineering (BPR) in the modern business world, thus illustrating the theoretical and practical concept of BPR, the applications of BPR, the drivers of BRR (in terms of internal drivers and external drivers), the critical success factors of BPR (i.e., egalitarian leadership, collaborative working environment, top management commitment, supportive management, information technology, change management, project management, and cross-functional coordination), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 139 publications
0
6
0
Order By: Relevance
“…Hence, continual business changes have become a norm. To combat, companies go for business process management (BPM) (Jeston, 2014) and business process reengineering (BPR) (Kasemsap, 2015; Thompson et al , 2009). BPM has gained significant attention.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, continual business changes have become a norm. To combat, companies go for business process management (BPM) (Jeston, 2014) and business process reengineering (BPR) (Kasemsap, 2015; Thompson et al , 2009). BPM has gained significant attention.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al (2015) stated that the staff performance, lead shortening in internal processes, quality, and cost will also be improved with the BPR. Kasemsap (2015) also showed that applying the BPR will greatly improve the business functionality and help to achieve the commercial objectives in the international enterprise. Kasemsap (2020) argued that applying the BPR in e-Government has the potential to enhance the public sector performance, transparency, and decrease costs, resource requirements and help to reach the business purposes in public companies.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Consequently, organizational changes have been motivated by exterior innovations, rather than by the internal factors of organizations. In [9], [10], the authors emphasized that organizations which decline to adopt innovative changes and advancements can be subsequently left behind. Therefore, organizations which have attempted business process changes are likely to achieve spectacular performance improvements and attain competitive advantages [9], [11].…”
Section: A Business Process Changementioning
confidence: 99%
“…In [9], [10], the authors emphasized that organizations which decline to adopt innovative changes and advancements can be subsequently left behind. Therefore, organizations which have attempted business process changes are likely to achieve spectacular performance improvements and attain competitive advantages [9], [11]. For the time being, organizations must face recent technology developments, and must determine how to adapt to these changes [3].…”
Section: A Business Process Changementioning
confidence: 99%
See 1 more Smart Citation